Apples to kangaroos: A framework for developing internationally comparable carbon emission factors for crop and livestock products. (15th December 2016) - Hawkins, Jacob; Ma, Chunbo; Schilizzi, Steven; Zhang, Fan
Abstract: Consumption-based greenhouse gas accounting, which encompasses emissions from a nation's domestic final consumption as well as emissions embodied in imports, is gaining favor in the climate change literature for its effectiveness and consideration of equity. Unfortunately, the calculation of emissions embodied in the trade of agricultural food products is hindered by a lack of consistent and comparable emission factors. Food import quantities for every country are readily available through the United Nations Food and Agriculture Organization. Unfortunately, the carbon emission factors necessary to calculate the embodied emissions in imported foods are largely unavailable or unreliable for many countries. On top of this, different methodologies for determining carbon emission factors provide varying estimates based on different assumptions. The differences in these assumptions and methodologies can mean that attempts to compare and combine emissions based on factors from different countries become less of a comparison of apples-to-apples and more of an apples-to-oranges or even apples-to-kangaroos exercise. This study proposes a method to combine the Food and Agriculture Organization's available greenhouse gas data, production data, and agricultural yields and scaling it against benchmarks in the literature to estimate a time-series of crop and livestock carbon emission factors that are internally consistent within the Food and Agriculture Organization's data set and comparable from nation to nation. The framework provided is then used to produce a sample set of carbon emission factors for Chinese agricultural import suppliers to determine the embodied greenhouse gases in China's food imports. Highlights: Using FAO data, we extrapolate comparable, consistent carbon emissions factors necessary for calculating embodied emissions in food products. China's imports from its top 14 food supply trade partners were responsible for 41 million tonnes of greenhouse gas emissions. China's 2009 food consumption produced 1.4 billion tonnes of greenhouse gas, with food imports contributing approximately 3% of this amount.